Improved wind system using non-linear power control - Yasmine IHEDRANE; Chakib El Bekkali; Madiha El Ghamrasni; Sara Mensou; Badre Bossoufi (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This article, present a new contribution to the control of wind energy systems, a robust nonlinear control of active and reactive power with the use of the Backstepping and Sliding Mode Control approach based on a doubly fed Induction Generator power (DFIG-Generator) in order to reduce the response time of the wind system. In the first step, a control strategy of the MPPT for the extraction of the maximum power of the turbine generator is presented. Subsequently, the Backstepping control technique followed by the sliding mode applied to the wind systems will be presented. These two types of control system rely on the stability of the system using the LYAPUNOV technique. Simulation results show performance in terms of set point tracking, stability and robustness versus wind speed variation.